Microorganisms in the biofertilization of corn crop as a complement to chemical fertilization - Canizalez-Silva, Manuel; Blanco-Macías, Fidel; España-Luna, Martha Patricia; de la Rosa-Rodríguez, Rodolfo; Lara-Herrera, Alfredo; Lozano-Gutiérrez, Julio (Ecosistemas y Recursos Agropecuarios, 2024)
In Mexico, the nutrients to the corn crop are supplied with chemical fertilizers, however, the price of these inputs requires looking for other alternatives to reduce costs, without reducing production. The objective of this work was to determine the individual and combined effect of Azospirillum brasilense, Bacillus subtilis, and Serendipita indica, (eight treatments) on corn production. The crop was established in Zacatecas, Mexico, under greenhouse conditions, in the year 2022. The microorganism’s inoculation was carried out at the sowing time. The eight treatments with microorganisms were evaluated in an experimental design in randomized blocks with four repetitions. With the co-inoculation of A. brasilense and S. indica the yield of the entire plant was increased, and the highest grain yield with A. brasilense and B. subtilis, this last increased, compared with the control treatment, it was 40%.